A New Method Calculating Stresses and Displacements in Elastic Bars - Górecki, Z.; Rybicki, J. (Engineering Transactions, 1987)
A new method is presented enabling rapid numerical evaluation of stresses and displacements of orthotropic, linear-elastic thin-walled bars of polygonal cross-sections. The algorithm is based on Vlasov’s shell theory. The differential equations derived are solved numerically by means of the method of splines. Examples of numerical results prove the possibility of application of the existing FORTRAN programs. The paper contains a novel formulation of the boundary conditions.